The health aspects of skiing - Maria Kubas; Katarzyna Krzemińska; Julia Czerwik; Julia Kuszneruk; Magdalena Kłusek; Katarzyna Chawrylak; Wojciech Kubas; Aleksandra Sadok (Quality in Sport, 2024)
Introduction and Purpose: